The influence of status and minimum facility requirement in gated and guarded landed terrace house in Nusajaya, Johore - Wong, Stella Chou Ping, 1985-; Ahmad Ariffian Bujang; Fakulti Kejuruteraan dan Sains Geoinformasi (2009)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2009